Kajian tindak balas bahan kimia ke atas pelbagai jenis fabrik untuk menghasilkan Tekstura - Lee,, Siew Hsia (Universiti Malaysia Sarawak (UNIMAS), 2007)
This research is focused on producing textures by using chemical substances. The analysis covers identification of chemical reaction with new fabrics. The shibori, tie, and stitches techniques were applied to produce 3D effects to the fabric surface. The end results successfully shows that certain chemical could enhance new and aesthetic look without ruined the quality of fabric.